The role of counterparty risk and asymmetric information in the interbank market - Giuseppe Cappelletti; Giovanni Guazzarotti (European Central Bank (ECB), 2017)
We study the effect of counterparty risk on the ability of Italian banks to access the foreign unsecured interbank market during the sovereign debt crisis in the second half of 2011. With the onset of the crisis, interest rates in the Italian interbank market soared and foreign lending decreased significantly. To isolate the effect of the rise in counterparty risk, we compare the funding of Italian banks with that of foreign banks. branches and subsidiaries in Italy, which were presumably unaffected by the sovereign crisis insofar as they could count on the actual or potential support of their parent bank. We find that the rise in counterparty risk substantially decreased the probability of obtaining funds from foreign banks. When the analysis is restricted to Italian and foreign banks with relatively comparable asset compositions, the result holds. In addition, where safer banks or more stable lending relationships are involved the effect is attenuated.
Keywords: G21; G28; C23; C24; 330; Interbank market; Counterparty risk; Financial crisis